WAQI’U TA’LIIM AL-NATSRI AL-ARABY BI INDONESIA - Ahsanuddin, Mohammad (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2016)
This research is to describe the teaching and learning of Arabic prose with regard to goals, themes, methods, media, and evaluation, as well as prose analysis examples made by both teacher and student. The research method used is descriptive-qualitative. The subjects are students at the Arabic Department who have taken Prose Analysis (Dirasah Natsriyyah) course. The result of the research shows that prose is an expression what lies in human’s heart. The goals of the learning is to understand theories used to analyze prose, and to apply them in text analysis. The themes studied included the understanding of prose, acquintance with some theoretical approaches for analysis, such as structuralism, semiotics, etc. The methods of learning employed are lecture, text analysis, and assignment. The media of learning used is power point. The evaluation is undertaken throughout the process of learning, in addition to what the students had achieved in their exams.